Effectiveness Of Coal Mining License Supervision By The Energy And Mineral Resources (ESDM) Department Of East East East Eastern Province In Samarinda City - Sunardi Syahhuri; Budiman, Budiman (Jurnal Ilmu Pemerintahan, 2021)
This study aims to describe and analyze the effectiveness of the supervision provided by the Office of Energy and Mineral Resources (ESDM) of the East Kalimantan Province in Samarinda City. This type of research is descriptive and qualitative approach. The data analysis technique uses descriptive qualitative data analysis, namely conducting data analysis based on the results of interviews. Data collection techniques using library research and field research include observation, interviews and documentation. The results of the study show that supervision of coal mining permits is still considered ineffective, this is because at the stage of achieving the objectives the supervision time is minimal because it is carried out once a year due to before and during the Covid-19 Pandemic the existing budget is limited, in the integration stage carried out it is felt lacking supervision carried out in moderation due to the Covid-19 Pandemic and inadequate facilities and infrastructure, lack of strictness in post-mining reclamation regulations which caused casualties, then the impact of the flooding that occurred and the efforts made were felt to be not effective enough because not all mining companies received supervision . Furthermore, at the adaptation stage, the existing supervisors are still lacking to carry out inspections due to the fact that the number of supervisors is only 35 people less than the number of mining permits so that several companies do not receive supervision. continuing to implement health protocols without supervision in the field using more online systems, this is not working properly. Factors constraining budget constraints, limited human resources, active or non-active status of the company and factors of distance & not being able to interact directly are spaciousness.